Implementasi DOMPES (Domino Pecahan Senilai) untuk Mendukung Literasi Numerasi Siswa Kelas IV SD - Ditasari, Denok Aulia; Primasatya, Nurita; Ibnu Zaman, Wahid (YASIN, 2026)
Numeracy literacy is a fundamental competency that needs to be developed from primary school, including through equivalent-fraction instruction, which requires an understanding of symbols, representations, and relationships among fractions. However, the use of domino game media that specifically integrate the concept of equivalent fractions with numeracy literacy activities remains limited. This study aimed to implement DOMPES (Domino Pecahan Senilai) and evaluate its validity, practicality, and effectiveness in supporting the numeracy literacy skills of fourth-grade primary school students. This study employed a quantitative approach using the Research and Development (R&D) method and the ADDIE model, which comprises the Analysis, Design, Development, Implementation, and Evaluation stages. The participants were fourth-grade students at SDN Gayam 3 Kota Kediri. Data were collected through observations, interviews, expert validation, teacher and student response questionnaires, and pretests and posttests, and were subsequently analyzed using quantitative descriptive analysis and normalized gain (N-gain). The results showed that DOMPES achieved a validity score of 88%, categorized as highly valid, and a practicality score of 94.81%, categorized as highly practical. The students’ mean score increased from 52.60 on the pretest to 92.95 on the posttest, with an N-gain value of 0.86, which was categorized as high. These findings indicate that DOMPES is a valid, practical, and effective concrete game medium for increasing student engagement, facilitating the understanding of equivalent fractions, and supporting the development of numeracy literacy skills. Future research is recommended to test DOMPES with larger samples and across broader school contexts using more robust experimental designs.